RANCANG ULANG USER INTERFACE DAN USABILITY TESTING TERHADAP SITUS WEB SISTEM INFORMASI AKADEMIK (SIKAD) ITENAS - AISYAH, NUR; WAHYUNING, CAECILIA SRI (e-Proceeding FTI, 2024)
The website-based Academic Information System (SIKAD) at the National Institute of Technology (ITENAS) is a platform that provides data information in the form of grade transcripts, class schedules, finances, guardianship, activities and lecture attendance. When interacting on the SIKAD ITENAS website, there is still misinformation and has not accommodated the real needs of users, so it needs to be redesigned according to user needs. The redesign of the User Interface (UI) refers to 5 usability aspects and is followed by usability testing based on a design thinking approach. This study involved 40 Industrial Engineering students for the questionnaire test and 5 Industrial Engineering students for the Think Aloud test. UI problems on this site are the information provided is not detailed, the selection of fonts and colors is not appropriate, the features do not meet user needs and the UI design is done on the homepage, features on the inquiry menu and other menus. The test results on the homepage, inquiry menu and other menus show that the results of the redesign of the SIKAD ITENAS website meet all aspects of usability, with a success rate of 100% and no errors in its implementation. Abstrak Sistem Informasi Akademik (SIKAD) berbasis website di Institut Teknologi Nasional (ITENAS) merupakan platform yang memberikan informasi data berupa transkrip nilai, jadwal perkuliahan, keuangan, perwalian, aktivitas dan kehadiran kuliah. Saat berinteraksi di website SIKAD ITENAS masih terdapat misinformasi dan belum mengakomodasi kebutuhan riil pengguna, sehingga perlu rancangan ulang sesuai dengan kebutuhan pengguna. Perancangan ulang User Interface (UI) mengacu pada 5 aspek usability dan dilanjutkan dengan usability testing berdasarkan pendekatan design thinking. Penelitian ini melibatkan 40 orang mahasiswa Teknik Industri untuk pengujian kuesioner dan 5 orang mahasiswa Teknik Industri untuk pengujian Think Aloud. Permasalahan UI pada situs ini adalah informasi yang diberikan tidak rinci, pemilihan font dan warna yang tidak sesuai, fitur belum memenuhi kebutuhan pengguna dan rancangan UI dilakukan terhadap halaman homepage, fitur-fitur pada menu inquiry dan menu lain-lain. Hasil pengujian terhadap halaman homepage, menu inquiry dan menu lain-lain menunjukkan hasil rancang ulang website SIKAD ITENAS memenuhi seluruh aspek usability, dengan nilai success rate 100% dan tidak terdapat error dalam pelaksanaannya.